Individual Power and Political Behaviors in Organizations: An Inadequately Explored Reality - Schein, Virginia E. (Academy of Management Review, 1977)
Despite their apparent pervasiveness, individual political behaviors in organizations have received minimal theoretical and research attention. This discussion focuses on individual power related behaviors. A conceptual scheme links: (a) the bases of individual power; (b) the intent of the powerholder; and (c) the means of the powerholder. Implications for related areas and suggested research approaches are discussed.